Identification and Prioritization of the Factors Affecting the Implementation of Activity-Based Costing with Analytic Hierarchy Process: Qaemshahr Municipality Case Study - Varadi, Seyedeh Shayesteh; Taghavi, Abbas (Journal of History Culture and Art Research, 2017)
The aim of the research is to identify and prioritize the factors affecting the successful implementation of Activity-Based Costing (ABC) system in Qaemshahr Municipality so that we can learn about the factors affecting the deployment of the ABC system in the organization under study. The present study is applied and descriptive-analytical (non-experimental) in terms of the objective and methodology, respectively. Statistical population of the study includes 35 managers, deputies and experts in finance and accounting department of Qaemshahr Municipality in 2016. The required data were collected using a validated questionnaire based on conceptual models; and the data were analyzed through Expert Choice and Topsis software. Research findings about the research questions show that from the perspective of managers, deputies and experts in finance and accounting department of Qaemshahr Municipality, parameters of: 1. Technical factors with the final weight vector of "0.389", 2. Individual factors with the final weight vector of "0.277", 3. Environmental factors with the final weight vector of "0.173", and 4. Organizational factors with the final weight vector of "0.161", are respectively the most important factors in the successful implementation and deployment of ABC system in Qaemshahr Municipality.